Sosialisasi Bahaya Narkoba dan Pelatihan Remaja Sebaya Peduli Anti-Narkoba di Kecamatan Parangloe (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
This Community Service Program (PKM) was conducted with the primary objective of enhancing understanding, awareness, and skills among youth in Parangloe District in preventing drug abuse. Drug abuse has become one of the greatest threats to the development of young generations in Indonesia, including in Parangloe District, which has begun to show indicators of increasing risk. This activity focused on education-based prevention efforts and youth empowerment through a peer educator approach, whereby youth were trained to become agents capable of disseminating information and positive influence within their communities. The program was implemented through a series of socialization sessions, seminars, interactive discussions, and peer youth training. The materials provided covered understanding various types of drugs, causal factors of abuse, health impacts, social and legal consequences, and prevention strategies applicable at the family, school, and community levels. The results demonstrated increased participant knowledge, formation of Peer Youth Groups Concerned with Anti-Drug Efforts, and growing commitment to undertake sustainable prevention measures. This PKM activity had a significant impact on strengthening social resilience in Parangloe District and building an active role for youth as pioneers of the anti-drug movement.